TRANSFORMATION OF STUDENTS' SOCIAL BEHAVIOR IN PECIMAS ACTIVITIES: A COLLABORATIVE APPROACH IN EDUCATION - Tio Budi Hartono; Achmad Hufad; Siti Komariah (Universitas Negeri Medan, 2025)
This essay examines how PECIMAS (Pelajar Cinta Masjid) activities at SMA Laboratorium Percontohan Indonesian University Education's influence students' social behavior. This descriptive qualitative study examines how religious activities in schools promote the internalization of values like responsibility, empathy, cooperation, and tolerance. It is driven by the growing worry over teenage moral degradation in the age of globalization. Symbolic interactionism and social action theory are used to evaluate activities such as shalat dhuha, Qur'anic tadarus, religious discourses, and Islamic events. The results show that PECIMAS's social interactions offer a contemplative environment that improves students' perceptions of themselves and helps them develop healthy social habits. Habitual behaviors, student involvement, outstanding role models, and the incorporation of religious principles into school culture are all examples of character development techniques. As a result, PECIMAS becomes a place for spiritual growth as well as a social learning environment that is contextual and transformative, fostering the growth of morally and religiously oriented people.